Challenges in the management of massive intraorbital and hemifacial arteriovenous malformation as causing life-threatening epistaxis - Manuel, A.M.; Kalimuthu, S.; Pathmanathan, S.S.; Narayanan, P.; Zainal Abidin, Z.; Azmi, K.; Khalil, A.A. (Elsevier, 2017)
Arteriovenous malformations are congenital lesions that may evolve with time and manifest in a plethora of presentations. They can occur as torrential epistaxis when it extensively involves the facial region. Multi-imaging modalities are available to assist in characterizing the structure of the lesion as well as its location and extent. This complex disease requires a multidisciplinary team approach with preoperative embolization and surgery. We present a rare cause of life-threatening epistaxis in a gentleman with a longstanding orbital and hemifacial arteriovenous malformation and discuss the complexities involved in its management.